The Effect of Transfer Pricing and Capital Intensity in Tax Avoidance - Ferdiansyah Ferdiansyah; Dwi Septiani; Sunarto Sunarto (Universitas Muhammadiyah Sorong, 2026)
This study aims to examine the effect of transfer pricing and capital intensity on tax avoidance simultaneously and partially in energy sector companies listed on the Indonesia Stock Exchange (IDX) for the 2019–2023 period. Tax avoidance, as a form of legal tax avoidance, is often carried out by companies through transfer pricing strategies between related entities and the use of high fixed assets to reduce tax burdens. This study is based on agency theory, which states that there is a conflict of interest between principals and agents, where managers can exploit loopholes in tax regulations for personal or corporate interests. This study uses a quantitative approach with an explanatory research method. The research sample consists of 7 energy sector companies selected through a purposive sampling method with a total of 35 observations over five years. Secondary data is obtained from published annual financial reports. The data analysis technique used is panel data regression, preceded by classical assumption tests and the selection of the best regression model through the Chow, Hausman, and Lagrange Multiplier tests. The results show that transfer pricing and capital intensity simultaneously have a significant effect on tax avoidance. Partially, transfer pricing has a positive and significant effect on tax avoidance, meaning companies tend to reduce their tax avoidance rates when transfer pricing practices are controlled. Conversely, capital intensity has no significant partial effect on tax avoidance. This finding suggests that high use of fixed assets is not necessarily a means of tax avoidance. The results of this study are expected to provide practical implications for the government in strengthening tax oversight policies and for companies in formulating compliant and efficient tax strategies.